Strategic Planning for Sustainable Economic Recovery in the New Normal Period in the City of Surabaya - Ignatia Martha Hendrati; Nuruni Ika KW; Kiky Asmara; Sebastiana Viphindrartin (Trunojoyo University of Madura, 2022)
The Covid-19 pandemic has had a considerable impact on the economy in the cityof Surabaya, especially in the fields of Micro, Small, and Medium Enterprises andthe creative industry, tourism, and employment. The City of Surabaya. By usingSWOT analysis, it can be concluded that although the economic growth of the Cityof Surabaya during the Covid-19 pandemic has decreased, the economic growthin the City of Surabaya is still positive and always above the national and EastJava economic growth and improved the economy after the covid pandemic. Theseinclude empowering MSMEs, integrating tourist destinations, both natural tourism,populist-based history, and religion, improving the quality of the workforce to suitthe company's needs, and so on.